(untitled) (Reflection and Critique Law Magazine, 2024)
this research aims to analyze the normative foundations that enable the performance of the Natura company, with regard to the economic benefit of natural substances in the environment, associating them with its cosmetic products. Thus, the general objective is to study Natura’s practices as a practice of economic development combined with environmental sustainability. And as a specific objective there is the reflection of the following national normative diplomas: the Federal Constitution of 1988 and the National Biodiversity Policy (Law 13,123/2015) which currently ensure Natura’s business performance in the management of biodiversity in its products. And to develop the research, the deductive hypothetical method was used, through the following question: what are the legal diplomas that enable the performance of the Natura Company, in relation to the economic benefit of the biodiversity used in its products, in view of the perspective of economic development and the one of environmental sustainability? The methodological procedures used were: bibliographic and documental survey.